Effects of Splenectomy on Immune Thrombocytopenic Purpura in (NZW x BXSB) F1 Mice: Analyses of Platelet Kinetics and Anti-Platelet Antibody Production - Mizutani, Hajime; Furubayashi, Takayasu; Kashiwagi, Hirokazu; Honda, Shigenori; Take, Hironori; Kurata, Yoshiyuki; Yonezawa, Takeshi; Tarui, Seiichiro; Ikehara, Susumu (Thrombosis and Haemostasis, 1992)
Effects of splenectomy on platelet kinetics and production of anti-platelet antibodies were studied in male (NZW × BXSB) F1 (W/B F1) mice, which are known as the animal model of immune thrombocytopenic purpura (ITP). Studies on organ localization of radiolabeled platelets revealed that splenic uptake significantly increases in W/B F1 mice in comparison with that of normal controls. W/B Fj mice showed a significant increase in platelet counts and, in contrast with sham-operated controls, high levels of platelet counts were maintained up to 6 weeks after splenectomy. Platelet lifespans (PLSs) did not reach normal levels, although prolonged PLSs were observed. In addition, platelet-associated antibody (PAA) values showed a tendency towards transient decrease, but there was no change in platelet-bindable serum antibodies (PBAs). These findings indicate that the suppression of anti-platelet antibody production is essential to the treatment of ITP; splenectomy may not be effective in treating severely affected ITP patients because, although the spleen is one of the major sites of platelet sequestration and antibody production, reticulo-endothelial systems (RESs) (liver, bone marrow, lymphnodes, etc.) other than the spleen are also responsible for the destruction of platelets. We therefore consider the W/B F1 mouse to be a useful model of human ITP, and believe that it provides valuable information for the development of new therapeutic agents in patients with ITP, especially those who do not respond to splenectomy.